Efecto de la temperatura de revenido en la resistencia a la corrosión por picaduras y localizada de un acero inoxidable austenítico AISI304. (2024)
This thesis project investigates the effect of tempering temperature on the pitting and intergranular corrosion resistance of AISI 304 austenitic stainless steel. The steel was subjected to solution treatment at 1100°C and tempered at 500°C, 550°C, 600°C, 650°C, and 700°C, followed by potentiodynamic and cyclic polarization tests in 3.5% NaCl. The results showed that tempering temperature significantly impacts corrosion resistance: lower temperatures improved pitting resistance, while higher temperatures enhanced intergranular resistance due to the formation and distribution of chromium carbides. These findings are crucial for material selection in industrial applications requiring high corrosion resistance, optimizing heat treatment processes to improve the durability and reliability of components.